Surgical Approaches in Spontaneous Osteonecrosis of the Knee: Systematic Review - Selawijaya, Yusuf (Seroja Husada: Jurnal Kesehatan Masyarakat, 2024)
Background: Spontaneous osteonecrosis of the knee (SONK) is a condition of acute, unilateral knee pain which is caused by destruction of knee’s bony structure. Non-surgical treatment could be effective for mild cases. However, surgical treatment should be considered in moderate to severe cases. This systematic review was aimed to determine the outcome of various surgical approaches in SONK patients. Methods: Systematic review was done in accordance to the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) statement. Searching was conducted on PubMed, ScienceDirect, Scopus, ClinicalKey, and Google Scholar. Criteria were set derived from the population of SONK, intervention of surgical methods, and outcome of clinical outcome, including efficacy and safety. Selected studies were appraised using critical appraisal tools by The- Joanna-Briggs Institute for inclusion. Included studies were extracted for characteristics and results, further being analyzed qualitatively. Results Nine studies were found – one discussing each of combination of osteochondral autograft transplantation (OAT) and concomitant high tibial osteotomy (HTO), HTO alone, and total knee arthroplasty (TKA). There were seven studies studying unicomparmental knee arthroplasty (UKA). OAT+HTO provided improvement in Knee Society Score (KSS) knee and function scores alongside 100% survivorship. HTO improved KSS knee and function scores. TKA has no significant complications. UKA was reported to improve KSS symptom, knee, function, patient activity, and patient satisfactory score; Oxford Knee Score (OKS); alongside with low revision and complication rates. Conclusions: Surgical approaches, regardless of the methods, were effective and safe way for treatment of SONK.